De París a Barcelona : la transferència de la modernitat vista per Ramon D. Perés - Gemma Bartolí Masons (Catalonia)
The article examines the opinion of the literary critic Ramon D. Perés about the arrival of literary and artistic modernity in Catalonia at the end of the 19th century. Perés notes that everything that came from Europe first passed through France, where not only texts but also translations were produced. However, opposed to the most innovative schools and fashions, the critic distanced himself from the most radical poetic renewal and ended up on the fringes of the movement that he himself had helped to develop.